2013
DOI: 10.1126/science.1235294
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Individuality in Genetically Identical Mice

Abstract: 41. Materials and methods are available as supplementary materials on Science Online. 42. One of the features of our approach is its ability to distinguish between antibodies targeting overlapping epitopes in a substantially different ways: There is a significant difference in the correlation coefficients for antibodies targeting a similar epitope versus the correlation coefficients for antibodies targeting different epitopes on the same site of vulnerability. Similarly, there is a significant difference for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

32
441
4
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 442 publications
(490 citation statements)
references
References 32 publications
32
441
4
3
Order By: Relevance
“…A likely source of disagreement may reside in the typical assumptions of twin and adoption studies. For instance, these studies usually assume no Gene ϫ Environment interactions, whereas in reality, such interactions are likely to exist (Freund et al, 2013). Nevertheless, environmental variables that may be associated with cognitive performance are typically not measured in quantitative behavior studies, which thus cannot assess the viability of the "no Gene ϫ Environment interaction" assumption (Hunt, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A likely source of disagreement may reside in the typical assumptions of twin and adoption studies. For instance, these studies usually assume no Gene ϫ Environment interactions, whereas in reality, such interactions are likely to exist (Freund et al, 2013). Nevertheless, environmental variables that may be associated with cognitive performance are typically not measured in quantitative behavior studies, which thus cannot assess the viability of the "no Gene ϫ Environment interaction" assumption (Hunt, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Several environmental factors may also influence the potential of expression of a trait, thereby influencing the phenotype expected for a given genotype. Hence, the same genotype may express differently in different, or even identical, environments (Freund et al, 2013;Hunt, 2011;Plomin, Haworth, et al, 2013). Moreover, it is recognized that for continuous traits, such as cognitive abilities, there is potential for additive genetic effects.…”
Section: Discussionmentioning
confidence: 99%
“…They drew their conclusion from a detailed analysis of social interactions among the mice based on joint spatial configurations derived from a video-based tracking system. In their discussion, Shemesh et al highlighted the suggestive relation of their data to our finding that genetically identical mice sharing one enriched environment for a period of 3 months developed stable behavioral trajectories that correlated with adult hippocampal neurogenesis as a measure of structural brain plasticity (Freund et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the original set-up for the study previously reported by us (Freund et al, 2013), we paralleled two identical experiments, (sharing one control group) the only difference being, that in one enclosure we assessed histological measures of adult neurogenesis at the end of the study, and in the second enclosure we performed a detailed behavioral monitoring. The aim of the behavioral monitoring had been to gain deeper insights into behavioral patterns beyond those assessable by the automated tracking system, for instance, signs of aggressiveness, play behavior, maintenance behavior, and social interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation